The induction of KLF4 expression by coupled epigenetic therapies: potential association with the WNT signalling pathway in colorectal cancer cells - Moodley, Natanya (My University, 2014)
Epithelial cancers such as colorectal cancers are highly predominant in the Southern African population, and are attributable to a number of factors, including genomic instability due to histone modifications and aberrant DNA methylation of gene promoters, as well as the inactivation of tumour-suppressor genes or the activation of oncogene pathways. The Wnt/β-catenin pathway plays a vital role in the regulation of intestinal epithelial cells, and is aberrantly activated in colon neoplasms. Krüppel-like factor 4 (KLF4) is a tumour suppressor gene that is hypermethylated at its promoter region and therefore down-regulated in colon cancer cells. This zinc finger transcription factor is crucial in colon cancer cells, where its induction has been proposed to regulate tumourigenesis. Over recent years, epigenetic modulators such as histone deacetylase (HDAC) inhibitors and DNA methyltransferase (DNMT) inhibitors have been investigated with regards to their potential anticancer activities. The following study assessed the in vitro effects of the HDAC inhibitor Valproic acid and DNMT inhibitor Zebularine on the expression of KLF4 in early (SW480) and late stage (DLD-1) colon cancer, and breast (MCF-7) cancer cells. At the onset, bioinformatics tools were utilised to predict and assess the methylation status and to examine methylation patterns within the KLF4 and CTNNB1 (β-catenin) genes. In association with this, methylated DNA within early and late stage colon cancer cells was quantified. Here, the 5’ untranslated region of KLF4 was highly methylated, while CTNNB1 displayed a low frequency of methylation. Following drug treatments, with Valproic acid and Zebularine respectively, gene expression profiles showed that high dosages increased the expression of KLF4 relative to low doses in early stage cancer cells; however the greatest induction of KLF4 was observed in late stage cancer cells in response to a high dose combination treatment with Valproic acid and Zebularine. CTNNB1 was antagonistically regulated relative to KLF4, wherein its expression was down-regulated post-treatment. Breast cancer cells surprisingly exhibited opposing results, with both KLF4 and CTNNB1 being up-regulated following high dose treatments, and the low dose treatments displaying the greatest anti-tumourigenic activities. Confocal microscopy results illustrated that KLF4 was localised in the nucleus and nuclear periphery, where it could associate directly with β-catenin. Thus in response to epigenetic therapy, KLF4 was differentially expressed in early and late stage colon cancer cells as a tumour suppressor. The down-regulation of β-catenin in colon cancer cells resulted in the suppression of the Wnt signalling pathway, thereby exerting anti-tumourigenic and anti-proliferative properties on the cells. Therefore, this study concludes that Valproic acid and Zebularine may serve as potential anti-cancer agents in the pursuit of an epigeneic therapy for colorectal cancer.
Keywords: Colorectal Neoplasms